Trzy wymiary użytecznego miasta - Maciej Błaszak, Maciej Błaszak; Artur Fojud, Artur Fojud (Człowiek i Społeczeństwo, 2016)
The paper analyzes three dimensions of the usable city: experiential, functional and rational. These dimensions are connected with three types of mental experiences, respectively, sensational, perceptional and conceptual, and with three neural networks: salience, central executive and default mode. It is argued that sensations refer to the physical space of the city, perceptions to the functional niche of the city, and concepts to the values implemented in the brain and recognized in the urban objects during their usage. The notion of the usable city is tightly connected with the notion of the happy city: three brain networks computing the information about dimensions of the usable city generate three parameters of happiness: pleasure, satisfaction, and one’s potential realization.